EFFECTIVE COMMUNICATION IN ISLAMIC ANTI-CORRUPTION EDUCATION - Agus Sucipto Roso; Hari Purwadi; Hartiwiningsih Hartiwiningsih; Faiqatul Isma Dwi Utami (Universitas Muhammadiyah Ponorogo, 2020)
Communication is a necessity in education. This study aimed at investigating howeffectiveness of communication in education world, especially in Islamic education.This study was literature study, meanwhile, data of this study was collected indocumentation by using descriptive approach as data analysis. Furthermore,communication has a role that cannot be separated in Islamic education. The exchangeof information from a teacher to a student must be occurred effectively. Teacher’sabilities and skills in communicating and conveying a message (science) are veryinfluential in learning process and lead to the results which are achieved by a studentor students. The better the teacher gives clear inputs and messages in education, thebetter the message received by student or students.